Exploring the barriers and facilities migrants face in accessing COVID-19 vaccines in Malaysia: A qualitative study. - Tharani Loganathan; Amirah Zafirah Zaini; Hazreen Abdul Majid (PLoS ONE)
Background Malaysia provided COVID-19 vaccines for all residents, regardless of citizenship status. However, the extent of vaccine accessibility for migrant populations remains unclear, given the complex healthcare barriers they face. This study explored the barriers migrants faced in accessing COVID-19 vaccines and the measures taken to facilitate their access. Methods This qualitative study, conducted between April 2022 and February 2023, involved 32 purposively selected key informants from non-governmental organisations (7), international organisations (2), labour unions (2), healthcare providers (11) and migrant communities (10). Data were collected through in-depth, semi-structured, primarily individual interviews, and analysed using NVivo 12 Pro software following a six-phase thematic analysis: data familiarisation, code generation, theme identification, theme review, theme definition, and reporting. Results Thematic analysis identified barriers-including legal and administrative challenges, digital exclusion, vaccine hesitancy, and logistical issues-and facilitators, such as mandatory vaccination policies, innovative delivery approaches, communication support, and community engagement. Substantial challenges arose from pervasive distrust in healthcare services, compounded by identity document requirements, roadblocks, and fears of immigration arrests. Digital appointment systems excluded many migrants due to language and literacy barriers, data privacy concerns, and the need for identity documents. While vaccine hesitancy among migrants was generally low, concerns were primarily driven by fears of immigration enforcement rather than vaccine safety. Despite vaccination being voluntary, mandatory requirements for digital vaccination certificates or negative COVID-19 test results strongly incentivised uptake. Employer support, driven by economic interests, played a critical role in promoting compliance with workplace vaccination mandates. Collaboration with non-governmental organisations and community partners proved pivotal, offering tailored health communication and building trust. Flexible vaccine delivery strategies, including a shift from centralised to outreach models near residences and workplaces, enhanced access, particularly for hard-to-reach populations. Conclusion Despite numerous challenges, Malaysia's vaccination efforts were largely successful due to innovative and collaborative delivery and communication strategies. To further improve health equity among marginalised populations, it is essential to enhance culturally sensitive training for frontline workers, strengthen employers' business ethics, and increase the involvement of trusted stakeholders.